Opportunities and Strategies for Da'wah of Muhammadiyah Aceh Organizations against Youth Trends in Coffee Shops in Banda Aceh City - Mauvizar, Erly; Rahim, Abdul; Zulisa, Eva (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The growth of number of Coffee shop becomes a trend to hangout for the youth in Banda Aceh. Habit of drinking coffee has become a wisdom for them. Gathering, hangout, appointment and making assignment are all being done in coffee shop. This opportunity is started to be aimed by one of the Islamic organization and society to do missionary endeavor or usually called as dakwah in coffee shop. The purpose of this research is to elaborate the opportunity and strategy of Association of Muhammadiyah Aceh, and also get around the trend of young generation lifestyle at coffee shop in Banda Aceh. The strategy that has been used for dakwah is through religion entertainment approach, spreading flyers and in advance, they are using youtube and social media which are interesting for the youth such as Tiktok. This research is using primary data approach such as interview, observation, and spreading google form. Furthermore, analyzing data is going to be done through SWOT analysis, data reduction and lastly composing the report.